Negotiating Mourning Norms: Living Fiqh of Ihdad among Widows in a Madurese Muslim Community - Soim (2 issues per year (June and December), 2025)
This study aims to examine how ihdad as an Islamic mourning obligation is understood, practiced, and negotiated in the everyday lives of widows within a Madurese Muslim community, where religious norms intersect with deeply rooted cultural expectations. Rather than treating ihdad as a fixed legal doctrine, the article explores its operation as a form of lived religious practice shaped by social pressure, economic necessity, religious literacy, and communal authority. Using a qualitative empirical legal approach, the research employs an in-depth case study conducted in a rural Madurese setting, drawing on semi-structured interviews with widows, religious leaders, and community figures, supported by participant observation and document analysis. The findings reveal that the implementation of ihdad is neither uniform nor purely doctrinal. While some widows adhere closely to classical fiqh prescriptions regarding duration, seclusion, and restrictions on adornment, others reinterpret or partially observe these norms due to livelihood demands, limited religious knowledge, or local customs. This variation illustrates the emergence of living fiqh, in which Islamic law is enacted through continuous negotiation between normative texts, cultural traditions, and social realities. Religious leaders and community norms play a decisive role in legitimizing particular interpretations, often prioritizing social harmony over strict legal formalism. The significance of this study lies in its contribution to socio-legal and religious studies by demonstrating how Islamic legal norms function as dynamic social practices rather than static rules. By foregrounding widows’ lived experiences, the article offers a nuanced understanding of how mourning, gender, and religious authority are negotiated in Muslim societies, thereby enriching broader discussions on religion, law, and social life within contemporary Muslim communities.